(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Plants have been used in traditional medicine to treat common human illnesses in our local communities. Crude aqueous and methanol extracts of Boswellia dalzielii stem bark were screened to investigate the phytochemicals responsible for its antimicrobial activity. The crude extracts and methanol extract fractions were used to conduct antimicrobial activity against some clinical isolates (Eschericia coli, Shigella dysenteriae and Salmonella typhi). Results of the antimicrobial activity showed that both methanol and aqueous extracts had activity against the clinical isolates with higher activity observed in the methanol extract against E. coli (16.670.96 at 500 mg/ml) and S. typhi (16.170.75 at 500 mg/ml). Bioassay of the partitioned methanol extract showed n-butanol had the best activity against the organisms and the n- butanol fractions were more active against E. coli (16.00±0.00), then S. dysenteriae (14.00±0.00) and least active against S. typhi (11.00±0.00) all at 50 mg/ml. The MIC of all the organisms for both methanol and aqueous extracts is 7.81 mg/ml but 15.63 mg/ml in methanol for S. dysenteriae and the MBC range between 7.81- 125 mg/ml in both extract for all the organisms. The results of this study therefore indicated that the plants’ stem bark contain potent phytochemicals which inhibited the growth of the tested clinical isolates which validate its continued use in traditional medicine to cure illnesses.